TEKNIK MENULIS YANG EFISIEN DAN EFEKTIF DI MEDIA ONLINE - Harahap, Arifin S. (Universitas Esa Unggul, 2019)
Writing news in online media are still many that do not meet the requirements. News is written too long and follows the writing style in print media. Writing news in online media must be efficient and effective to be easily scanned by readers. Efficient and effective is different from print and television media. Online media space is very limited compared to the two media. If the news is made too long and long-winded, the reader will quickly saturate and make them reluctant to read it. In fact, the language of news in online media must be pleasing, readable and easy to understand. This is what underlies the writing training in online media for Inews TV employees in December 2018. The training is conducted by providing material on how to write good news in online media. After that, the news will be analyzed in the Inews TV online media, whether it has fulfilled the provisions. The results of the analysis are monitored together, is there still a lack of writing in the next edition. This training is expected to make employees more adept at writing news in online media. After several times the training began to show better writing changesKeywords: Online media, efficient, effective